Obstetric intervention self-efficacy scale and the examination of obstetric intervention self-efficacy regarding department, grade level, and gender - K. Özdemir; A. Çevirme; S. Şahin; Ü. Sahranç; G. Durat; N. Uğurlu; Ö. Ertürk (Clinical and Experimental Obstetrics & Gynecology)
The aim of this study was to develop the Obstetric Intervention Self-Efficacy Scale (OISES). A sample of 327 university students (307 females, 20 males; 168 from the midwifery department and 159 from the nursing department) were enrolled in the study. Out of 66 items, the 22 items with the highest factor loadings were chosen as a result of preliminary exploratory factor analysis regarding 22 general obstetric intervention behaviors. The final exploratory factor analysis revealed that the 22 items of the OISES had a single factor and 67.21% of the total variance was explained by these items. Cronbach’s alpha reliability coefficient was calculated as 0.98. As a result, the overall findings demonstrated that this scale is a valid and reliable instrument. The analysis further revealed that OISES scores of students did change according to gender (females’ OISES scores were higher), department (midwifery students’ OISES scores were higher), and grade level (M4th > M1st, M2nd, & M3rd; M3rd > M1st & M2nd).